2017
DOI: 10.22489/cinc.2017.072-464
|View full text |Cite
|
Sign up to set email alerts
|

Arm-ECG Bipolar Leads Signal Recovery Methods for Wearable Long-term Heart Rate and Rhythm Monitoring

Abstract: A clinical database of distal electrogram recordings was created in conjunction with the Craigavon Area Hospital Cardiac Research Department. Signal averaged ECG (SAECG) methods were then used to inspect electrograms recorded bilaterally in a pilot study and the evidence based outcome of which directed the WASTCArD research group to consider the left arm as a prime location for a potential long term cardiac monitor. Empirical mode decomposition (EMD), ensemble empirical mode decomposition (EEMD) and data fusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…These values point out that the recorded signal indeed can be used, with minimal post-processing, for heartbeat rate calculation and therefore for arrhythmia detection since the vast majority of the heartbeats were correctly located. We found that the digitized experimental in-vivo recorded signals exhibited a higher SNR than most of the average values reported (after applying advanced denoising technics) in [4,42] (See Table 9). This suggests that the signals acquired with the WAMECG1 prototype are better in quality (less noisy) than the signals used by the previous studies.…”
Section: Discussionmentioning
confidence: 65%
“…These values point out that the recorded signal indeed can be used, with minimal post-processing, for heartbeat rate calculation and therefore for arrhythmia detection since the vast majority of the heartbeats were correctly located. We found that the digitized experimental in-vivo recorded signals exhibited a higher SNR than most of the average values reported (after applying advanced denoising technics) in [4,42] (See Table 9). This suggests that the signals acquired with the WAMECG1 prototype are better in quality (less noisy) than the signals used by the previous studies.…”
Section: Discussionmentioning
confidence: 65%
“…Experimental wearable ECG devices currently under development include T-shirts, vests, belts, patches and armbands [7]. In this context, armband devices are convenient for long-time recording on the upper arm and previous research carried by our team [8] confirmed the feasibility of denoising, processing , analysing, and extracting information from low-amplitude far-field ECG potentials [9].…”
Section: Introductionmentioning
confidence: 93%
“…For each recorded subject, signal-to-noise ratio (SNR) measurements from each of the selected arm bipolar leads, after the application of a data-driven signal denoising process (DWT or EMD), will be compared with SNR measurements obtained after applying the SA denoising control technique on corresponding arm bipolar leads [5][6].…”
Section: Denoising Performancementioning
confidence: 99%
“…With CVD and lethal heart arrhythmias continuing to have a high mortality rate, it is important to provide patient compliant solutions for non-invasively monitoring the heart rhythm information in the P-QRS-T interval of the ECG from a long-term wearable device placed on comfortable positions of the body, such as along a single arm (armband) [4], or if possible, on the wrist. The challenges of this approach lie in the difficulty of detecting an adequate bipolar ECG signal due to the low amplitude and excessive muscle artefact in these so called "far-field ECG" locations [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation